Vagal Nerve Stimulation for Refractory Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The tolerance and efficacy of periodic left vagal nerve (VN) stimulation in 12 children with medically intractable epilepsies are reported from the Sections of Neurology and Neurosurgery, Children's Mercy Hospital, Kansas City, MO.